2022
DOI: 10.5468/ogs.22053
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial thickness and uterine artery Doppler parameters as soft markers for prediction of endometrial cancer in postmenopausal bleeding women: a cross-sectional study at tertiary referral hospitals from Vietnam

Abstract: ObjectiveTo determine the value of endometrial thickness (ET) and Doppler indices of uterine artery (UtA) as sonographic markers in predicting endometrial cancer (EC) among postmenopausal bleeding (PMB) women in low-resource settings as Vietnam.MethodsThis cross-sectional study was conducted at the Hue University Hospital and Hue Central Hospital between June 2016 and June 2019. The study enrolled all women who complained of PMB and were followed by transvaginal Doppler ultrasound. Their definitive histopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…Overall, endometrial hyperplasia should be carefully managed by clinicians to avoid progression to moderate-severe anemia in women with perimenopausal bleeding, and abnormal endometrium thickness is a risk factor for endometrial cancer in women with postmenopausal bleeding. 6 , 7 , 13 , 38 Our study indicated no significant correlation between Hb concentration and endometrial thickness; however, the greater measured uterine size appeared to be associated with lower Hb levels. In fact, a large uterus may be accompanied by bulky fibroids, as well as other intrauterine masses, thus leading to severe hemorrhage and anemia.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Overall, endometrial hyperplasia should be carefully managed by clinicians to avoid progression to moderate-severe anemia in women with perimenopausal bleeding, and abnormal endometrium thickness is a risk factor for endometrial cancer in women with postmenopausal bleeding. 6 , 7 , 13 , 38 Our study indicated no significant correlation between Hb concentration and endometrial thickness; however, the greater measured uterine size appeared to be associated with lower Hb levels. In fact, a large uterus may be accompanied by bulky fibroids, as well as other intrauterine masses, thus leading to severe hemorrhage and anemia.…”
Section: Discussioncontrasting
confidence: 49%
“… 9 , 10 Ultrasonography has been described as giving gynecologists a second set of eyes, because it can reveal changes in uterine size as well as structural abnormalities in the uterine cavity. 11 , 12 , 13 These non-invasive findings are more acceptable first-line imaging modalities than invasive modalities such as endometrial biopsy or hysteroscopy. 4 , 14 Moreover, some studies have attempted to find correlations between the uterine size or endometrial thickness and the hemoglobin (Hb) concentration; however, the results remains limited in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, this should have been performed for the evaluation of HMB possibly associated with malignant disease. 9 The patients' symptoms in these cases were relieved by hormone therapy; therefore, no surgical treatment was performed. Whether hormone therapy will be effective in similar cases in the future requires accumulation of similar cases.…”
Section: Discussionmentioning
confidence: 94%
“…Ideally, this should have been performed for the evaluation of HMB possibly associated with malignant disease. 9…”
Section: Discussionmentioning
confidence: 99%
“…These modalities may be ultrasound, saline infusion sonography, computerized tomography scanner, magnetic resonance imaging, hysteroscopy, endometrial biopsy, etc. [ 14 15 16 17 18 ] However, some modalities remain expensive for assessment in low- and middle-income countries such as Vietnam. Meanwhile, the physician can firstly approach to initial features, evaluate carefully clinical symptoms, and classify the degree of anemia prior to investigate by additional diagnostic modalities as ultrasound, biopsy, and surgical procedures.…”
Section: Introductionmentioning
confidence: 99%